Readability and Suitability Evaluation of Educational Media Regarding Men\'s Secondhand Smoke on Pregnant Wives - Zohreh Karimiankakolaki; Vida sadat Anoosheh; Fatemeh Aliakbari (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: The tools for assessing the appropriateness of educational materials are measuring device. Suitability offers a systematic approach to objectively assessing the appropriateness of health information material for a specific audience. The present study is designed to evaluate the readability and suitability of educational media about regarding men's secondhand smoke (SHS) in the smoker men on their the exposure of pregnant wives. Methods: This analytical cross sectional study was done from October to December 2018 in Isfahan, Iran. Participants were in two groups. The first group of educational media audience consisted of 20 smokers with a pregnant wife. The second group was 15 people from the panel of experts. Written educational media (pamphlets) were evaluated. The readability of the material was measured by "readability assessment of materials" (RAM) and suitability was retrieved through "suitability assessment materials" (SAM).  The Gunning-Fog Index was used to assess the readability of the media and the cloze test was used to assess the educational level of the media. Descriptive indices were stated for all variables. The collected data were analyzed by SPSS18. Results: The readability mean score of the educational material was 16.60±1.34 for pamphlet, which was acceptable (score>10, P <0.001). Results showed the percentage points SAM score for the pamphlet was 85%. The educational material for media was "excellent" on the SAM rating. The score of the Gunning-Fog index for pamphlets was 9.6 and equivalent to the third grade of guidance was obtained. According to the evaluation by cloze test, pamphlet learning was assessed as an independent training without the need for a teacher. Conclusions: The printed materials were well-matched after evaluation by the RAM and the SAM checklist, the Gunning-Fog Index and the cloze test. They were consistent with the characteristics of smoker men.